On-Chip Scalable Resonator-Based Transducers for Terahertz Dielectric Sensing in SiGe BiCMOS Technology - Defu Wang; Klaus Schmalz; J Borngräber; Dietmar Kissinger (2018 Asia-Pacific Microwave Conference (APMC), 2018)
This paper presents two scalable resonator-based transducers (RBTs) at terahertz (THz) frequency range to realise THz spectroscopy for dielectric sensing. First, the design of 0.24 THz RBT is described by scaled a 0.12 THz sensing structures which utilises a wavelength-long closed-ring resonator to place inside of the Coplanar stripline (CPS) to make a high-selective bandpass response and combines with short-ended strips to create the bandstop behavior. Its scattering parameter can have a very large magnitude change and resonance frequency shift for the loaded samples. Next, a ring structure is also presented to implement 0.48 THz sensing by scaled a low frequency RBT, which employs ring resonator with an asymmetrically loaded stubs to perform a high analytic sensitivity and selectivity for loaded samples. Both presented scalable transducers, possessing the high integration capability of silicon circuits, are proved to be the promising employments in THz spectroscopy.